Non-Operatively Managed Primary Small Bowel Volvulus: A Case Report - Ewnte, Biniam; Tadesse, Robel (Archives of Clinical and Medical Case Reports, 2022)
Background: Primary small intestinal volvulus is one of the common causes of intestinal obstruction in various localities of the developing world. Although operative intervention has been the usual mode of treatment; this case report depicts with meticulous follow-up & care, there is a possibility for relief of obstruction with non-operative management. Case Presentation: This is a case report of a 20-year-old male patient presented with crampy abdominal pain and frequent bilious vomiting. Plain abdominal film showed multiple distended small bowel loops with air fluid level, consistent with small bowel obstruction. Ruling out other etiologies primary small bowel volvulus was entertained and naso-gastric tube inserted, patient catheterized and kept nil per oral. After 48 hours of admission all symptoms resolved the patient resumed feeding and was discharged home. Conclusion: The reported case shows evidence in which the patient’s primary small bowel volvulus was relieved non-operatively with insertion of naso gastric tube keeping nil per oral.